Representasi Pendewasaan Usia Perkawinan Iklan BKKBN “Yakin Siap Nikah?” di Channel Youtube Dalam Perspektif Semiotika - Syafruddin Pohan; Billy Betha Nagara; Sofya Rahma Nasution; Wanti Isadora Br Simbolon (DIGICOM : Jurnal Komunikasi dan Media, 2023)
Abstract Child marriage is still a serious problem in Indonesia, prompting BKKBN to conduct a campaign for marriage-age maturity through an ad called "Yakin Siap Nikah?" aired on its YouTube channel. This research aims to analyze the denotative, connotative, and mythic meanings contained in the "Yakin Siap Nikah?" ad. This study uses a qualitative research method with Roland Barthes' semiotic analysis. The results show that, denotatively, the advertisement is published on YouTube to inform about the campaign for the maturity of marriage age. Connotatively, the advertisement contains meanings that can be seen in the storyline, acting, and writing, with the hope that the message intended for the audience is conveyed and understood. Meanwhile, mythically, this advertisement is a cultural institution's way of promoting itself through YouTube, with the philosophy of the message implied through the meaning of symbols and other characters such as the symbol of no smoking, paper airplanes, kites, and doves.